Normalization of Teleconsultations from Patients’ Perspectives: A Qualitative Longitudinal Study - Binder, Piotr (Inclusive Digital Technologies: Perspectives, Opportunities, and Limitations, 2025)
Tis chapter explores the popularization of teleconsultations as a form of remote medical carewithin Poland’s public healthcare system. It highlights how these practices have been adapted andthe challenges faced in making them a stable part of patients’ everyday routines. Te analysis isbased on qualitative longitudinal research conducted across three waves between 2020 and 2022,including interviews with young adults, parents of young children, and seniors (n = 356). Techapter reconstructs how perceptions of teleconsultations have evolved, examining the argumentsand experiences that infuence patients’ evaluations of remote medical interactions. Te interpretiveframework is based on normalization process theory, which enables analysis of the shif fromthe rapid expansion of remote-capable primary healthcare practices during the early phase of thepandemic to the subsequent slowdown and reversal of this trend in later stages. Te fndings revealthat, despite the swif expansion of teleconsultations and the ongoing development of e-healthtools, these consultations have been selectively and conditionally integrated into the patient-physicianrelationship. Tey are primarily viewed as a complement to in-person interactions, ratherthan as a complete replacement. Positive evaluations of past teleconsultations encourage their usein specifc situations. However, the degree to which these practices become established is limitedand is strongly infuenced by health-related contexts and previous interactions with the publichealthcare system.